Properties and Role of Exopolysaccharides Produced by Paenibacillus alvei NRC14 for Cell Protection - Abdel-Aziz, Shadia M.; Hamed, Hoda A.; Fadel, M.; Moharam, Maysa E. (IJRDO-Journal of Applied Science, 2015)
The interest in polysaccharides produced by microorganisms has increased considerably in recent years, as they are candidates for many commercial applications in different industrial sectors. In this study, exopolysaccharides produced by the bacterial strain Paenibacillus alvei NRC14, under normal and abiotic stress conditions, was investigated. The strain was found to produce exopolysaccharides (EPSs) possess different characteristics such as the sugar content and flocculating properties. The EPS production was 3.2 g/L under stress conditions. The chemical analyses indicated that it is a glycoprotein composed of polysaccharide (85%) and protein (12%).The molecular weight of the EPSs from strain NRC14 were 7.6 x 105 and 5.4 x 106 Da under the normal and acidic pH, respectively. The flocculation activity of EPSs ranged from 95 to 97.8 % in less than 48 hrs of growth. Under normal conditions, the produced EPSs have shown to consist of aminosugars and has good flocculating activity, whereas the EPSs were greatly affected with the abiotic stress conditions. FTIR spectrometry of the EPSs indicated presence of carboxyl, hydroxyl, and amino functional groups which are the principles for the flocculating properties.